MECHANICAL EQUIPMENT INVESTMENT ANALYSIS TO MEET PRODUCTION TARGETS AT PT ABC, NORTH BENGKULU - R. Fajri.B; F. Mahdyrianto; M. Puspita (Jurnal Pertambangan, 2026)
The reallocation of production equipment to a subsidiary in 2025 significantly reduced fleet availability at PT ABC, preventing the company from meeting its annual coal production target of 617,000 tons. This decline in productivity necessitates immediate and meticulous investment planning for additional mechanical units to ensure long-term operational continuity. This study aims to analyze the requirements for loading and hauling equipment, calculate investment cost components, and determine the most efficient procurement scheme among cash purchase, leasing, and rental. Utilizing the Discounted Cash Flow (DCF) method, the research evaluates investment criteria such as Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PBP), while conducting a sensitivity analysis on coal price fluctuations and operational costs. The results indicate that the leasing scheme is the most profitable alternative, yielding the highest NPV of IDR 12,877.68 million, an IRR of 27.45%, and a payback period of 3.45 years. Sensitivity analysis reveals that a 5-10% decrease in coal prices exerts a more significant impact on declining profitability compared to an equivalent increase in operational costs. Consequently, the leasing scheme is recommended as the primary strategic choice due to its superior initial cash flow flexibility and market risk resilience.